The SAS programmer's PROC REPORT handbook ODS companion - Eslinger, Jane (SAS Institute, Inc., 2018)
Annotation
Includes bibliographical references and index. - Online resource; title from title page (viewed March 30, 2018)
Keywords: SAS (Computer file); SAS (Computer program language); SAS (Langage de programmation); COMPUTERS; Mathematical & Statistical Software